2009
DOI: 10.1248/bpb.32.631
|View full text |Cite
|
Sign up to set email alerts
|

Potent Bactericidal Constituents from Mallotus philippinensis against Clarithromycin and Metronidazole Resistant Strains of Japanese and Pakistani Helicobacter pylori

Abstract: In the quest for potent anti-Helicobacter pylori agents, we found 70% EtOH extract of Mallotus philippinensis (LAM.) MUELL. (MPM) with strong bactericidal activity at the concentration of 15.6-31.2 mg/l against eight H. pylori strains. Further fractionation and purification of 70% EtOH extract of MPM led to the isolation of 5 compounds, namely 5,7-dihydroxy-8-methyl-6-prenylflavanone (1), 3 -prenylrubranine (2), red compound (3), isorottlerin (4), and rottlerin (5) which were elucidated on the basis of nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…13,14) Several studies have reported the anti-H. pylori activity of herbal medicines and the chemical constituents therein. [15][16][17] Furthermore, anti-adhesion activity against H. pylori binding to gastric epithelial cells has been proposed as a potential therapeutic strategy to prevent H. pylori colonization which is an initial step of the infection. 18) Resveratrol, firstly described to be the content of weed Polygoumum cuspidatum, is highly abundant in red grapes and reasonably abundant in blueberries and peanuts.…”
mentioning
confidence: 99%
“…13,14) Several studies have reported the anti-H. pylori activity of herbal medicines and the chemical constituents therein. [15][16][17] Furthermore, anti-adhesion activity against H. pylori binding to gastric epithelial cells has been proposed as a potential therapeutic strategy to prevent H. pylori colonization which is an initial step of the infection. 18) Resveratrol, firstly described to be the content of weed Polygoumum cuspidatum, is highly abundant in red grapes and reasonably abundant in blueberries and peanuts.…”
mentioning
confidence: 99%
“…Among the isolated compounds, rottlerin (98), exhibited the most potent bactericidal activity with a minimal bactericidal concentration (MBC) value of 3.12-6.25 mg/l against several clinical H. pylori isolates including Japanese and Pakistani strains, nine clarithromycin resistant (CR), and seven metronidazole resistant (MR) strains. This study thus revealed the potent in vitro anti-H. pylori activity of the ethanolic extract and of rottlerin, specially against CR and MR strains, which could be gainfully utilized for the development of novel antimicrobials to prevent H. pylori related disorders (Zaidi et al 2009). …”
Section: Antimicrobial Activitymentioning
confidence: 87%
“…Four phloroglucinol derivatives (kamalins) were isolated from M. philippinensis, including rottlerin (98) and isoallorottlerin (99) (Lounasmaa et al 1975). Isorottlerin (100) was also mentioned in M. philippinensis (Zaidi et al 2009). …”
Section: Phloroglucinol Derivatives (Table 14)mentioning
confidence: 99%
See 1 more Smart Citation
“…Kamala 5, 7-dihydroxy-8-methyl-6-prenylflavanone, 3'-prenylrubranine, red compound, isorottlerin, rottlerin 50 .…”
Section: Mallotus Philippensis Euphorbiaceaementioning
confidence: 99%